KAJIAN ANTITESIS HEGELIAN DALAM ARSITEKTUR - Muhammad Nurwahyu; Murni Rachmawati; Josef Prijotomo (ATRIUM: Jurnal Arsitektur, 2015)
Title: Study of Hegelian Antithesis in Architecture This paper tries to expose hegelian antithesis existence, that can be used as a way of thinking in architecture design process. With antithesis that lies in philosophy scope, then it needs to be settled with similar thing in architecture. The settlement will be set by using descriptive critique method. The result of the settlement can become a starting point for the usage of Hegelian antithesis in architecture design exploration. In this paper, antithesis proven to be equal with architecture of difference as bildung. Those equality shown in the architecture dialogue. With this equality, antithesis become defined and known its position in architecture.